ESTIMATES OF GREEN'S FUNCTION FOR SECOND-ORDER PARABOLIC EQUATIONS NEAR EDGES. Issue 2 (17th April 2015) - Kozlov, V. A.; Rossmann, J.
Abstract : We consider the first boundary value problem for a second-order parabolic equation with variable coefficients in the domain K× R^n-m, where K is an m -dimensional cone. The main results of the paper are pointwise estimates of the Green's function.